PENINGKATAN HASIL BELAJAR FISIKA PESERTA DIDIK MELALUI MELALUI PEMBELAJARAN TEAMS GAMES TOURNAMENT - Eni Sumanti Nasution (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
This study aims to determine the application of cooperative learning models of the Teams Games Tournament (TGT) type on learning to improve student learning outcomes. The subject of this research was the tenth grade students of SMAN 1 Batang Onang. This type of research is Classroom Action Research. The research design used was the Kemmis and Mc model. Taggart which includes the stages of planning, action and observation, and reflection. The data collection instruments used were observation sheets, student activity scale, and LKS. The data analysis technique used is descriptive qualitative and quantitative data analysis. Based on the results of data analysis in the first cycle of meeting I showed an increase in student mathematics learning outcomes. Research Results, namely an increase in student learning outcomes The average grade value when the pre test is only 38.67. The class average value increased by 63 in cycle I. The average grade value in the first cycle still did not meet the KKM set by the school. In the second cycle the average value of the class experienced an increase of 85.33. Classical learning completeness in the first cycle was only 53%. In cycle II classical learning completeness becomes 96%. This shows an increase in students' classical learning completeness by 43%. Keywords: Teams Games Tournament (TGT) Learning Model, Learning Outcomes